Prospective randomized comparative study of pigtail catheter drainage versus percutaneous needle aspiration in treatment of liver abscess - Kulhari, Mukesh; Mandia, Rajendra (ANZ journal of surgery, 2019)
Background This prospective randomized comparative study is designed to compare outcomes of ultrasonography‐guided pigtail catheter drainage (PCD) and needle aspiration for the treatment of liver abscesses in terms of days to achieve clinical improvement, 50% reduction in cavity size and duration of hospital stay. Methods This is a hospital‐based comparative study conducted in SMS Hospital, Jaipur, India, from May 2015 to May 2017. Sample size was calculated to be 95 subjects in each of the two groups at α error of 0.05 and power of 80%. Independent t‐test was used for statistical analysis. Results A total of 190 patients of liver abscess were included in this study and we treated 95 patients with percutaneous needle aspiration (PNA) and remaining patients with PCD along with systemic antibiotics. Mean time for clinical improvement in PNA group (6.96 ± 1.33 days) was higher as compared to PCD group (4.22 ± 1.25 days). The mean time for reduction of cavity size to 50% of original size in PNA group (7.05 ± 1.25 days) was higher as compared to PCD group (4.43 ± 1.27 days). Mean hospital stay of patients in PNA group (12.9 ± 4.02 days) was higher as compared to PCD group (11.44 ± 4.15 days). Conclusion Percutaneous catheter drainage is a better modality as compared to PNA especially in larger abscesses which are partially liquefied.